Phāra nāthī khō̜ng nāyok ratthamontrī khon thī 24 Phon ʻĒk Surayut Čhulānon (s.n., 2007)
Pictorial presentation on activities and duties of the 24th prime minister of Thailand, 1 October 2006 - 29 January 2008, General Surayut Chulanon.